Tidal-induced Dilution of Ammonia - Nitrogen (NH3-N) along Batang Salak - Dunging, Buda; Ling, Teck Yee; Nyanti, L.; Norhadi, Ismail (-, 2013)
NH3-N is an important parameter considered for water quality monitoring. High NH3-N contents in the river system may lead into euthrophication. Tidal flushing in the river determines the assimilation capacity of the river system affected by the tide. Therefore. the objective of this study was to monitor the tidal effect on the NH3-N dilution in the Batang Salak. The study conducted along Batang Salak comprised eight stations during nebb tide. The first round of sampling started at 0900 hr during low tide with the highest NH3-N concentration found at station 8. NH3-N ranged from 0.47 mg/L - 2.86 mg/L. The 0900 hr trip corresponded with the decrease in tide level that brought the upstream farm discharge water of Loba Kara channel into Loba Bodoh where station 8 is located. NH3-N recorded among station during 0900 hr trip was significantly different. Second round started at 1200 hr during low tide with station 6 showing the highest NH3-N concentration. NH3-N ranged from 1.17 mg/L - 3.03 mg/L. The high NH3-N was likely due to the location of station 6 at Loba Kara estuary where the high tide water mixed with the prawn farm effluent. Third and fourth round started during high tide at 1500 hr and 1800 hr and NH3-N concentrations ranged from 3.04 mg/L - 5.87 mg/L and 0.75 mg/L 4.43 mg/L respectively. Station 6 and Station 4 showed the highest NH3-N concentration during 1500 hr and 1800 hr respectively. Station 6 still had the highest NH3-N as the previous round at 1200 hr. The highest NH3-N at Station 4 at 1800 hr was due its at the upstream of the Loba Kara where the pond farm effluents discharged was brought back upstream by the peak high tide at 1700 hr. NH3-N concentration at 1500 hr was significantly higher compared to NH3-N recorded during 900hr, 1200 hr and 1800 hr. This study indicated the possibility that the pond effluent was discharged during high tide. Tide level thus influences the NH3-N content in the river where the 1500 hr was the highest and slowly dropped following the tide level.